Cardiovascular Disease and HIV Infection in Sub-Saharan Africa: Misplaced Priorities in the Public Health and Research Agendas? - Bain, Luchuo Engelbert; Gwain, Gerald Chia (Frontiers in Cardiovascular Medicine, 2019)
The effectiveness of combined antiretroviral therapy, not only allows people living with HIV (PLHIV) to live longer, but also exposes them to extra cardiometabolic risks. The recent report of the International AIDS (Acquired Immune Deficiency Syndrome) Society and the Lancet commission are clear on the fact that, the world is not on track regarding ending the HIV/AIDS pandemic by the year 2030 (UNAIDS 90 – 90 -90 targets). We highlight the priority public health interventions, as well as research actions to cope with this almost inevitable triple burden of disease for the continent. Improvement of routine data collection within the health systems strengthening agenda, prioritization of primary health care as the cornerstone of an effective health care system to contain HIV as a chronic disease, and multiplication of large cohort studies in Sub – Saharan Africa are the main public health and research imperatives.